Antibacterial Activity From Cucumber (Cucumis sativus .L) Ethanol Extract In Deodorant Roll On Dosage Form - Laila Susanti; Subur Widodo; Qurrota Aini; Dyah Rahmawati (Indonesian Journal of Pharmaceutical Science and Technology, 2017)
Body odor of human skin usually occur due to excessive production of sweat glands couples with the presence of bacteria. The active ingredient to prevent body odor are chemicals materials from alum or sodium in order to have negative effects such as skin irritation, Alzheimer disease, prostate and breast cancer. Natural materials technology has been development as an active agent by using cucumber (Cucumis sativus .L). The purpose of this research to conduct a deodorant roll on a stable and qualified physical quality and also develop the use of extract cucumber as an antibacterial Staphylococcus epidermidis. Cucumber extraction has been done by maceration with ethanol 70% for 4 days and then divided into three formulation extract (5%, 10%, and 20% (b/v)). All of the formulations has been tested by zone inhibition, organoleptic, homogenity, pH, viscosity and irritation test. The results given that all of the formulations meet the quality requirements of physical and the best formulation extract 20% able to inhibit bacterial by 26 mm as a largest diameter of the inhibitory zone. In addition the stability of deodorant roll on form were performed accelerated stability test for 35 days at room temperature (28°C) and 40°C. The test results indicate that the stability of the extract 10% quali ed physical quality during storage at room temperature (28°C) and high temperature (40°C) for 35 days. While in the extract 20% at high temperature (40oC) physical changes characterized by the deposition. Keyword : cucumber, deodorant roll on, antibacteria